Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1371/journal.pone.0131280
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of the Prefoldin Subunit 5 Gene Deletion in Canine Mammary Tumors

Abstract: BackgroundA somatic deletion at the proximal end of canine chromosome 27 (CFA27) was recently reported in 50% of malignant mammary tumors. This region harbours the tumor suppressor gene prefoldin subunit 5 (PFDN5) and the deletion correlated with a higher Ki-67 score. PFDN5 has been described to repress c-MYC and is, therefore, a candidate tumor-suppressor and cancer-driver gene in canine mammary cancer. Aim of this study was to confirm the recurrent deletion in a larger number of tumors.MethodsDroplet digital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
1
11
1
Order By: Relevance
“…However, it has been shown to be a tumor suppressor candidate in leukemia and tongue cancer [ 38 ]. The outcomes herein revealed higher expression in non-neoplastic tissue, suggesting it as a potential tumor marker just as demonstrated by Hennecke and colleagues [ 15 ]. Moreover, a previous study demonstrated that PFDN5 was recurrently deleted in CMT [ 26 ].…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…However, it has been shown to be a tumor suppressor candidate in leukemia and tongue cancer [ 38 ]. The outcomes herein revealed higher expression in non-neoplastic tissue, suggesting it as a potential tumor marker just as demonstrated by Hennecke and colleagues [ 15 ]. Moreover, a previous study demonstrated that PFDN5 was recurrently deleted in CMT [ 26 ].…”
Section: Discussionsupporting
confidence: 82%
“…The gene expression profile of the mammary tumor in dogs is, to date, not well characterized and the use of tumor markers is still for research purposes only [ 15 ]. The analysis and differentiation of the mammary tumors is the basis for pathogenesis, diagnosis, prognosis, new therapy options, and good breed hygiene practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, other hormone receptors such as prolactin receptor (PRLR) or growth hormone receptor (GHR) have been evaluated in human breast cancer [ 10 11 ]. As approximately 50% of mammary gland tumors in dogs appear to be malignant [ 12 13 ], the detection of novel canine tumor markers with a value for prognosis or targeted therapy are the focus of research [ 14 19 ]. Therefore, in the present study, the gene expression of ESR1, PGR, PRLR and GHR were analyzed simultaneously to compare their distribution in canine mammary tissue.…”
Section: Introductionmentioning
confidence: 99%